Economic volatility and institutional reforms in macroeconomic policymaking: The case of fiscal policy - Adam Geršl; Jan Zápal (Charles University in Prague, Institute of Economic Studies (IES), 2010)
We evaluate proposals for independent fiscal authority put forward as a solution to excessive public spending. Our main conclusion is that moving the responsibility to set broad measures of fiscal policy from the hands of government to an independent fiscal council is not necessarily welfare improving. We show that the change is welfare improving if nature of uncertainty between fiscal and monetary policymakers does not change as a result. However, if this institutional change involves considerable decrease of capacity of the new agency to recognize economic shocks, citizens' welfare can decrease as a results. This is especially significant in times of increased economic volatility such as in a recent global financial crisis. Faced with the ambiguous theoretical result, we try to gain deeper insight by calibrating our simple model.
Keywords: E42; E58; E63; H30; 330; dynamic inconsistency; fiscal and monetary policy interaction; independent fiscal council; Finanzverfassung; Institutioneller Wandel; Finanzpolitik; Haushaltskonsolidierung; Finanzkrise